Pesantren On Digital Era: Tantangan Dan Peluang Pondok Pesantren As’adiyah Sengkang-Sulawesi Selatan - Abd. Haris Haris; Nurfaika (Innovations in Multidisciplinary Education Journal, 2024)
This article seeks to reveal the opportunities and challenges that are being faced by islamic boarding schools in this digitalization era, especially the As'adiyah Sengkang Islamic boarding school in South Sulawesi. The diversity of religious understandings that are being experienced by a plural society has resulted in contestation in digital spaces in order to maintain the community it considers the most correct, and tends to corner other groups.  On the one hand, there is a moral, moral degradation for millennials. The issues that will be studied in this article, first, how the role of the As'adiyah Islamic boarding school in the digital space.  Second, how is the strategy of the As'adiyah Islamic boarding school in facing challenges in the media space.  Third, what are the forms of opportunities for As'adiyah islamic boarding schools in the digital space. This research is a library research. Data collection utilizes written documents and the author's experience as an alumnus. This study found that the role of As'adiyah islamic boarding schools can be seen from the vision and mission of proselytizing transmission from as'adiyah voice radio (RSA) to as'adiyah Channel. Classical scientific characteristics (turats) and their educational transformation. As for the strategy of the As'adiyah islamic boarding school, for example, relations with the melenial community, building communication and having future characteristics. And furthermore, as an opportunity for Pesantren As'adiyah is a competitive pesantren, looking at the internal and external orientation of pesantren, displaying the local distingtions of Bugis pesantren both social culture, culture, and customs. Build relationships with As'adiyah branches inside and outside South Sulawesi. And the last is that the As'adiyah pesantren must digitize manuscripts, manuscripts of pesantren that have not been published.